Inactivation of Microcystis Aeruginosa by peracetic acid combined with ultraviolet: Performance and characteristics. (1st January 2022) - Cao, Lisan; Wang, Jingwen; Wang, Zongping; Yu, Shiwen; Cheng, Yujie; Ma, Jun; Xie, Pengchao
Highlights: UV/PAA process was efficient in algae inactivation. HO and RO played important roles with RO being dominant. Hom model described the algae inactivation kinetics well. HCO3 − promoted the inactivation efficiency. UV/PAA process performed better in natural water. Abstract: The inactivation of algae by a combined process of peracetic acid and ultraviolet irradiation (UV/PAA) was systematically investigated by choosing Microcystis aeruginosa as the reference algal species. Both hydroxyl (HO ) and organic radicals (RO ) contributed to the cell integrity loss and RO played the dominant roles. The algae inactivation kinetics can be well fitted by the typical Hom model, showing that the inactivation kinetic curves followed a type of shoulder and exponential reduction. The initial shoulder might be induced by the protection from the cell wall. Although the results from the cell morphology, UV–vis spectra and fluorescence excitation-emission matrices analysis suggested the cell lysis and the release of algal organic matter (AOM) in the UV/PAA process, the AOM could be subsequently degraded. Humic acid (1 − 5 mg/L) inhibited the algal cell inactivation, and the presence of chloride (0.5 − 2 mM) had little effect on the cell viability reduction. However, the addition of bicarbonate (1 − 5 mM) promoted cell integrity loss. The UV/PAA process displayed better performance under the natural water background, demonstrating the extensive potential for the practical application of this approach. This study suggests that the UV/PAA process is an effective strategy for algae inactivation. Graphical abstract: Image, graphical abstract